Tele-supervised home-based transcranial alternating current stimulation (tACS) for Alzheimer’s disease: a pilot study - Cappon, Davide; Fox, Rachel; den Boer, Tim; Yu, Wanting; LaGanke, Nicole; Cattaneo, Gabriele; Perellón-Alfonso, Ruben; Bartrés-Faz, David; Manor, Brad; Pascual-Leone, Alvaro (Frontiers in Human Neuroscience, 2023)
Background: Over 55 million people worldwide are currently diagnosed with Alzheimer’s disease (AD) and live with debilitating episodic memory deficits. Current pharmacological treatments have limited efficacy. Recently, transcranial alternating current stimulation (tACS) has shown memory improvement in AD by normalizing high-frequency neuronal activity. Our goal was to assess the safety, feasibility, and preliminary effects on episodic memory of a study companion-led home-based tACS approach (HB-tACS). Method: Eight participants diagnosed with AD underwent high-definition HB-tACS (40 Hz, 20-minutes) targeting the left angular gyrus (AG), a key node of the memory network. The Acute Phase comprised 14-weeks of HB-tACS with at least five weekly sessions. Three participants underwent resting-state electroencephalography (EEG) before and after. Subsequently, participants completed a 2–3-month Hiatus phase not receiving tACS. Finally, in the Taper phase, participants received 2-3 sessions per week over 3-months. Primary outcomes were memory and global cognition, measured with the Memory Index Score (MIS) and Montreal Cognitive Assessment (MoCA), respectively, and EEG theta/gamma ratio. Results reported as mean±SD. Result: All participants completed the study with, on average, 97 HB-tACS sessions; reporting mild side effects during 25% of sessions, moderate during 5%, and severe during 1%. Acute Phase adherence was 98±6.8% and Taper phase was 125±22.3% (rates over 100% indicates participants completed more than the minimum of 2/week). After the Acute Phase, all participants showed memory improvement, MIS of 7.25±3.77, sustained during Hiatus 7.00±4.90 and Taper 4.63±2.39 phases compared to baseline. For the three participants that underwent EEG, a decreased theta/gamma ratio in AG was observed. Conversely, participants did not show improvement in the MoCA, 1.13±3.80 after the Acute Phase, and there was modest decrease during the Hiatus -0.64±3.28 and Taper -2.56±5.03 phases. Conclusion: This pilot study shows the feasibility of a novel, remotely supervised, study companion-led HB-tACS intervention for AD. Targeting the left AG, memory in this sample was improved. These are preliminary results that warrant larger more definite trials to further elucidate tolerability and efficacy of this intervention. NCT04783350